Skadisotoma, a new genus of Isotomidae (Collembola) from Australia - Greenslade, Penelope; Fjellberg, Arne (Zootaxa, 2015)
A new species and genus, Skadisotoma inpericulosa, is described from south-eastern Australia. It possesses some characters that are found in Tomoceridae, such as a long cylindrical dens that is medially bent and a mucro with at least six teeth of different sizes and three setae but in other characters it resembles an isotomid. In this it shows similarities to the Boreal genus Mucronia Fjellberg, but differs from it in the possession of spines on the dens and in some chaetotaxic characters.